Efektifitas Pemberdayaan Kelompok Ibu Rumah Tangga Dalam Peningkatan Pengetahuan, Sikap Dan Praktek Pemberantasan Demam Berdarah Dengue Di Kelurahan Adiarsa Barat Kabupaten Karawang Provinsi Jawa Barat - Imas Masturoh (Loka Litbang Kesehatan Pangandaran, 2009)
Abstract. Adiarsa Barat village is one of endemic area of the Dengue Haemorrhagic Fever (DHF) in Karawang. That village had not touched by community empowerment yet. The purpose of this research was to know effectiveness of housewives empowerment for eradication of DHF with breeding site control. This research was an experimental quation, with intervention in one location and control in other. The final result was hoped that the respondents would increase of knowledge, attitude and practice. The data of housewife behaviour was collected by intervew. This research found that there was the increase of housewife’s group behaviour, followed by the increase of housewifes behaviour at intervention area with P value < 0,05. Although housewifes behaviour at control area hasn’t increase with P value > 0,05.This reaserch suggested that people participation needed to be identified first then monitored periodically, so that their behaviour to eradicate DHF disease would be a habit or permanent.